2023
DOI: 10.3389/fmolb.2023.1275774
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of acute myeloid leukemia cells to ferroptosis and evasion strategies

Hanyun Zhang,
Chunjie Sun,
Qi Sun
et al.

Abstract: Acute myeloid leukemia (AML) is a highly aggressive hematologic malignancy with a 5-year survival rate of less than 30%. Continuous updating of diagnostic and therapeutic strategies has not been effective in improving the clinical benefit of AML. AML cells are prone to iron metabolism imbalance due to their unique pathological characteristics, and ferroptosis is a novel cell death mode that is dominated by three cellular biological processes: iron metabolism, oxidative stress and lipid metabolism. An in-depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 167 publications
0
5
0
Order By: Relevance
“…Accordingly, a large body of work has recently highlighted the role of ferroptosis in acute myeloid leukemia (AML). Metabolic pathways typically altered in AML and related to ROS/RNS production include enzymes like nitric oxide synthase (NOS), CYP, NAD(P)H oxidase (NOX), and COX (reviewed in [ 70 ]). The high frequency of ROS/RNS overproduction in leukemia clearly implies that they are related to the etiology of this disease [ 71 ].…”
Section: Ferroptosis As a Biological Program: Features And General Me...mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, a large body of work has recently highlighted the role of ferroptosis in acute myeloid leukemia (AML). Metabolic pathways typically altered in AML and related to ROS/RNS production include enzymes like nitric oxide synthase (NOS), CYP, NAD(P)H oxidase (NOX), and COX (reviewed in [ 70 ]). The high frequency of ROS/RNS overproduction in leukemia clearly implies that they are related to the etiology of this disease [ 71 ].…”
Section: Ferroptosis As a Biological Program: Features And General Me...mentioning
confidence: 99%
“…Low levels of ROS, on the other hand, protect AML cells from apoptosis and increase treatment resistance, cell migration, growth, and proliferation [ 61 , 74 ]. AML cells are particularly sensitive to iron overload, and although there is strong evidence that transferrin is highly expressed in these cells with increased binding activity, the exact effect of transferrin on AML cells is unclear [ 70 ]. Therefore, ferroptosis is emerged as a therapeutic target in leukemia.…”
Section: Ferroptosis As a Biological Program: Features And General Me...mentioning
confidence: 99%
“…Furthermore, an emerging understanding of the role of tumoral angiogenesis and the impact of endothelial cell subsets in shaping BM niches have been reported [39]. Moreover, it is relevant to note that AML cells can use different strategies to avoid ferroptosis cell death, controlled by three main cellular processes: iron metabolism, oxidative stress, and lipid metabolism [40]. Additionally, transcription factors, such as HOXA9, are overexpressed in approximately 70% of AML cases with poor prognosis, increased chemoresistance, and higher relapse rates [41].…”
Section: Disease Overview and Aml Pathophysiologymentioning
confidence: 99%
“…This NES interacts with the nucleus cell exporter Exportin-1 (XPO1), causing accumulation of the NPM1 mutant in the cytoplasm [60,61]. The overexpression of the HOX gene [40], similar to KMT2A rearranged AML, guides the NPM-1 mutated AML development. Notably, overlapping features between t-NPM1 and de novo NPM1 AMLs suggest they can represent a single disease entity [67].…”
Section: Disease Overview and Aml Pathophysiologymentioning
confidence: 99%
“…Importantly, the same authors also reported that AML cells were unable to synthetize cysteine from methionine providing an opportunity to exploit this vulnerability for AML treatment. Of note, AML patients with high SLC7A11 mRNA expression exhibited a drastically lower overall survival than patients with low SLC7A11 expression [ 42 , 43 ].…”
Section: Targeting Gpx4 and Ferroptosis In Amlmentioning
confidence: 99%